Jutaku: Japanese houses - Pollock, Naomi 1971- (Phaidon Press, 2015)
"Featuring more than 400 houses - one per page, one image per house - Jutaku: Japanese Houses is a fast-paced, shock to the system that shines a Harajukubright neon light on the sheer volume, variety and novelty of contemporary Japanese residential architecture. Featuring the work of many of Japans̕ most famous architects including Shigeru Ban, Sou Fujimoto, Toyo Ito, Kengo Kuma, Jun Igarishi, Shuhei Endo and dozens of up and coming or as yet unknown young architects, Jutaku is organized geographically, speeding readers on a bullet train journey across Japans̕ architectural landscape."--
Keywords: Geschichte 1998-2014; Stadthaus; Einfamilienhaus; Japan; Bildband